1988
DOI: 10.1902/jop.1988.59.11.714
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Interactions with Dentin Specimens after Demineralization Using Tetracycline

Abstract: Greater cell attachment to demineralized dentin has been associated with subsequent development of a fiber attachment system. The purpose of this study was to evaluate tissue interactions to dentin demineralized with different concentrations of tetracycline solution. Dentin specimens were obtained from beneath root surfaces covered by periodontal ligament. Each rectangular specimen had a face of root surface dentin and an opposite surface of pulpal dentin. Experimental specimens were treated with a tetracyclin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
3

Year Published

1989
1989
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 29 publications
0
13
0
3
Order By: Relevance
“…Supportive periodontal therapy (SPT) comprises the mechanical removal of supra-and subgingival plaque and calculus [1,2] to achieve biological compatibility of root surfaces, thereby allowing reattachment of adjacent tissues [3][4][5][6]. To do so, scaling is performed using hand [7,8], ultrasonic [7,9,10] or sonic instruments [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Supportive periodontal therapy (SPT) comprises the mechanical removal of supra-and subgingival plaque and calculus [1,2] to achieve biological compatibility of root surfaces, thereby allowing reattachment of adjacent tissues [3][4][5][6]. To do so, scaling is performed using hand [7,8], ultrasonic [7,9,10] or sonic instruments [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…[19] In a study by Frantz and Polson, greater number of attached cells were found at 100 mg/ml of tetracycline HCl concentrations as compared to untreated controls. [24] Terranova et al also used the same concentration and found favorable results. [4] In case of EDTA, the concentration mostly used was in the form of a gel having 24% EDTA.…”
Section: Discussionmentioning
confidence: 96%
“…As fibroblast adhesion and locomotion is facilitated by collagen, [64][65][66] and smear layer prevents it. The delicate balance of these two factors is vital to fibroblast attachment and both the factors determine the number of fibroblast attachment.…”
Section: Discussionmentioning
confidence: 99%